PERBEDAAN STRAIN DAN UMUR BETINA TERHADAP JUMLAH KETURUNAN LALAT BUAH (Drosophila melanogaster Meigen) - Taufika, Ramadhan (Jurnal TAMBORA, 2020)
A study was conducted on the differences in strain and female age on the number of descendants of fruit flies (Drospohila melanogaster Meigen) to determine the effect of strain and female age on the number of D. melanogaster offspring in normal, taxi and sepia strains. Five D. melanogaster ? normal crossed with 5 D. D. melanogaster ? normal, 5 D. melanogaster ? taxi crossed with 5 D. D. melanogaster ? taxi, 5 D. D. melanogaster ? sepia crossed with 5 D. D. melanogaster ? sepia. Age of the crossed female is 8-10 hours, 12-14 hours, 16-18 hours, 20-22 hours, and 24-26 hours after hatching from the pupa. Each group of crosses was repeated five times. D. melanogaster crossing was carried out at 25oC. Data were analyzed with factorial anava and then tested further with LSD (Least Significant Difference) of 5% significance level. Based on the results of the study note that there is an influence of strain and female age on the number of offspring. It is also known that normal strains produce the highest number of offspring, whereas taxi strains produce the fewest offspring. Age of females 20-22 hours produces the most number of offspring and is not significantly different from females 24-26 hours, while ages 8-10 hours produce the fewest number of offspring and are not significantly different from ages 12-14 hours.